2016
DOI: 10.1259/bjr.20150492
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of cone beam CT in the adaptive radiotherapy planning process for non-small-cell lung cancer patients

Abstract: Objective: To investigate the potential use of cone beam CT (CBCT) in adaptive radiotherapy (ART) planning process for non-small-cell lung cancer (NSCLC). Methods: 17 retrospective patients with NSCLC Stage T1-T4, who had completed a course of radiotherapy with weekly CBCT imaging were selected for the study. The patients had been delineated and planned for threedimensional (3D) conformal treatment (prescription: 55 Gy in 20 fractions) based on free-breathing fourdimensional CT data. Of these initial 17 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…Michenzi et al assessed the accuracy of CB-CT for quantifying NSCLC tumor volume changes and reported a high correlation between CB-CT and the gold standard contrast-enhanced diagnostic CT ( 42 ). In our study, continuous tumor shrinkage during radiotherapy was detected to an extent in line with other studies reporting residual volumes of 49–75% and volume decreases of 1.2–1.5% per fraction ( 15 , 16 , 43 , 44 ). However, detection of treatment response and volume changes of mediastinal lymph node involvement was found to be challenging on CB-CT. Berkovic et al also emphasized that CB-CTs lack contrast to truly distinguish between lymph node and other surrounding tissue, which only allows for adaptation on the lung-lymph node boundary ( 17 ).…”
Section: Discussionsupporting
confidence: 92%
“…Michenzi et al assessed the accuracy of CB-CT for quantifying NSCLC tumor volume changes and reported a high correlation between CB-CT and the gold standard contrast-enhanced diagnostic CT ( 42 ). In our study, continuous tumor shrinkage during radiotherapy was detected to an extent in line with other studies reporting residual volumes of 49–75% and volume decreases of 1.2–1.5% per fraction ( 15 , 16 , 43 , 44 ). However, detection of treatment response and volume changes of mediastinal lymph node involvement was found to be challenging on CB-CT. Berkovic et al also emphasized that CB-CTs lack contrast to truly distinguish between lymph node and other surrounding tissue, which only allows for adaptation on the lung-lymph node boundary ( 17 ).…”
Section: Discussionsupporting
confidence: 92%
“…tumour shrinkage, atelectasis or pleural effusion), or displacements of anatomical structures (e.g. a baseline shift of the tumour or a shift of the mediastinal structures) needing adaptations occur in approximately 12-27% of the patients during fractionated radiotherapy [1][2][3][4][5][6][7]. As a result, the delivered dose to the tumour or organs at risk may deviate from the planned dose and become unacceptable [4,8].…”
Section: Introductionmentioning
confidence: 99%
“…Modern linear accelerators are integrated with a kilovoltage imaging system capable of cone-beam computed tomography (kV-CBCT), 1 which is increasingly utilized for verification of patient alignment, 2 evaluation of organ motion using pre-and posttreatment imaging, 3 and implementing adaptive radiotherapy planning. 4 It has also enabled sufficiently small margins for SBRT, often making dose escalation possible. 5,6 Onboard kV-CBCT is also increasingly being used for accurate patient setup in stereotactic radiosurgery (SRS).…”
Section: Introductionmentioning
confidence: 99%